A multidimensional and analytical perspective on Open Educational Practices in the 21st century - Brandenburger, Bonny (Frontiers in Education, 2022)
Already at the beginning of the 20th century, English educator and philosopher John Dewey emphasized the importance of learners having a say in their education and developing into mature subjects under democratic principles (Dewey, 1903). The fact that increased learner participation has a positive effect on the learning process and learning success is not new. Nonetheless, participatory approaches to teaching and learning are experiencing a new lease on life in the 21st century as a result of the rapid technology development. Knowledge, practices, and tools can be shared across spatial and temporal boundaries in higher education by means of Open Educational Resources (OER), Massive Open Online Courses (MOOCs), and open-source technologies. The Open Education Movement has further stimulated the discourse on openness in education and calls for new didactic approaches that encourage greater learner participation in formal higher education (Bedenlier, 2015, Muñoz et al., 2014). Based on a representative literature review and focus group research, I have developed an analytical framework that enables researchers and practitioners to assess the form of participation in formal, collaborative teaching and learning practices. The analytical framework is focused on the micro-level of higher education (teaching and learning processes), in particular on the interaction between students and lecturers when organizing the curriculum. For this purpose, I reflect anew on the concept of participation, taking into account existing stage models for participation in the learning context. I bring these together with the dimensions of teaching and learning processes, such as methods, learning objectives and content, etc. This paper aims to make a valuable contribution to the opening up of learning and teaching, and expands the discourse around possibilities for interpreting Open Educational Practices (OEP).